2014
DOI: 10.1002/ijc.28754
|View full text |Cite
|
Sign up to set email alerts
|

Potentially malignant disorders of the oral cavity: Current practice and future directions in the clinic and laboratory

Abstract: Despite commendable progress in the prevention, detection, and treatment of a wide variety of solid tumor types, oral squamous cell carcinoma (OSCC) remains a significant health burden across the globe. OSCC carcinogenesis involves accumulation of genetic alterations that coincide with the multistep malignant transformation of normal oral epithelium. OSCC is often first diagnosed at late stages of the disease (advanced regional disease and/or metastasis). Delayed diagnosis precludes successful treatment and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
161
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(194 citation statements)
references
References 136 publications
(154 reference statements)
2
161
0
13
Order By: Relevance
“…The less promising results of the randomized, placebo-controlled chemoprevention trials and further development of dietary chemoprevention agents were recently discussed. 47 Of note, a meta-analysis on beta-carotene supplementation and cancer risk (published after the authors commenced this RCT) reported on the absence of any protective effect associated with supplementation for various sites with regard to cancer risk. 49 Data from this study does not support the recommendation of beta-carotene combined with vitamin C for the chemoprevention of oral cancer when tested on otherwise healthy subjects living in well-nourished countries.…”
Section: Cancer Therapymentioning
confidence: 99%
“…The less promising results of the randomized, placebo-controlled chemoprevention trials and further development of dietary chemoprevention agents were recently discussed. 47 Of note, a meta-analysis on beta-carotene supplementation and cancer risk (published after the authors commenced this RCT) reported on the absence of any protective effect associated with supplementation for various sites with regard to cancer risk. 49 Data from this study does not support the recommendation of beta-carotene combined with vitamin C for the chemoprevention of oral cancer when tested on otherwise healthy subjects living in well-nourished countries.…”
Section: Cancer Therapymentioning
confidence: 99%
“…3 Oral cancer carcinogenesis involves the accumulation of genetic alterations leading to the multistep malignant transformation of normal oral epithelial cells. 4 Currently, the exact mechanism is unclear; thus, further understanding and identification of factors that initiate disease and modify disease outcomes, such as immune-cancer interactions and interplay between oral bacteria and host immune responses, will contribute to better prevention and patient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[2] OSMF has the potential to progress to oral squamous cell carcinoma (OSCC). [3] Every year, OSCC is estimated to occur in more than 400,000 people worldwide. [4] Every year, 120,000 deaths occur due to OSCC.…”
mentioning
confidence: 99%
“…[4] Every year, 120,000 deaths occur due to OSCC. [3] Currently, there are several modes of management of OSCC and OSMF, depending upon the stage of the disease and several other factors. The 5-year survival of OSCC patients still remains to be 50%.…”
mentioning
confidence: 99%